2022
DOI: 10.4236/cus.2022.104032
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Land Regularization in Accessing Credits from Financial Institutions in Tanzania

Abstract: A linkage between land regularization and access to credit has been a policy priority in developing countries including Tanzania. However, formal credit markets in these countries are underdeveloped and expectations that land titling through land regularization improves access to credit are muted. A study to examine the implication of land regularization in accessing credit from formal financial institutions in Tanzania was carried out in two areas of Kimara and Buhongwa Wards in cities of Dar es salaam and Mw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In a study in Buhongwa and Kimara, Mbilinyi et al (2022) found that land regularisation had insignificant implications to credit access, because most land owners with certificates of right of occupancy had no enabling environment to link legally documented plots with formal financial institutions to support household activation of investment on land. According to Benjamin et al ( 2020), properly arranged land ownership systems influence agricultural productivity and production through effective land security and investment demand.…”
Section: Land Ownershipmentioning
confidence: 99%
“…In a study in Buhongwa and Kimara, Mbilinyi et al (2022) found that land regularisation had insignificant implications to credit access, because most land owners with certificates of right of occupancy had no enabling environment to link legally documented plots with formal financial institutions to support household activation of investment on land. According to Benjamin et al ( 2020), properly arranged land ownership systems influence agricultural productivity and production through effective land security and investment demand.…”
Section: Land Ownershipmentioning
confidence: 99%